2014
DOI: 10.3855/jidc.4035
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Trypanosoma cruzi infection in blood donors in El Salvador between 2001 and 2011

Abstract: Introduction: El Salvador is regarded as a highly endemic country for Chagas disease, as evidenced by the relatively high estimated positive serology rate for Trypanosoma cruzi among blood donors. This study aimed to identify the factors contributing to this high rate by analyzing changes in T. cruzi seroprevalence. Methodology: Secondary data were collected from 31 blood banks operated by the Ministry of Health, the Red Cross, the Institute of Salvadoran Social Security, and the Military Hospital. The data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
0
11
0
3
Order By: Relevance
“…The overall seroprevalence among pregnant women registered at the three health centres was 3.6%, higher than among blood donors in Sonsonate province (2.9%) and El Salvador's national average (1.7%) (Sasagawa et al . ) but lower than among adults in Sonsonate province (8.0%) (Cedillos et al . ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The overall seroprevalence among pregnant women registered at the three health centres was 3.6%, higher than among blood donors in Sonsonate province (2.9%) and El Salvador's national average (1.7%) (Sasagawa et al . ) but lower than among adults in Sonsonate province (8.0%) (Cedillos et al . ).…”
Section: Discussionmentioning
confidence: 90%
“…, ) and blood donors at blood banks (from 3.7% in 2001 to 1.7% in 2011) (Sasagawa et al . ) but also among pregnant women. This corroborates the contribution of socio‐economic improvement to reduction in seroprevalence among pregnant women in Bolivia from 27.6% in 1992–1994 to 17.3% in 1999–2001 (Torrico et al .…”
Section: Discussionmentioning
confidence: 99%
“…According to WHO estimates, El Salvador is the fifth most affected Latin American country, with a prevalence of 1.3% [4]. However, two recent studies of pregnant women and blood donors living in the departments of Sonsonate and Ahuachap an found prevalence rates of 3.8% and 2.5%, respectively [18,19], and it has been reported that the prevalence of CD among Salvadoran immigrants living in Los Angeles is 3.4% [20]. There is little information about the prevalence of CD among Salvadorans living in Europe: the above mentioned metaanalysis [5] that included 67 Salvadoran migrants found a pooled prevalence of 3.7%: three times that estimated in El Salvador by the WHO [4].…”
Section: Discussionmentioning
confidence: 99%
“…13 The seroprevalence among pregnant women (3.8%) was twice as high as seroprevalence among children under 15 years of age (1.9%) in Santa Isabel Ishuatán in [2007][2008][2009] (Table 1) and also national average seroprevalence among blood donors aged 18 years or older (1.7%) in El Salvador in 2011. 24 This implies that pregnant women should be the higher priority subgroup in the National Chagas Disease Control Program than other age groups. Note that we cannot determine that pregnant women are exposed to higher risk of being infected with T. cruzi than other age groups, as this study has limitations in assessing whether they had been infected during their pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Technical quality of works of the laboratory is regularly monitored both internally by conducting a routine self-assessment and externally by requesting a Brazilian institute (Fundação Pró-Sangue, Hemocentro de São Paulo) to annually double-check the results of serological tests. 24 For those whose ELISA IgG test results were positive, an additional ELISA IgG test was undertaken by applying Chagatest IHA (Wiener Lab.) to venous blood samples collected during follow-up home visits.…”
Section: Methodsmentioning
confidence: 99%